Probing Context-Dependent Modulations of Ipsilateral Premotor-Motor Connectivity in Relapsing-Remitting Multiple Sclerosis - Ruiu, Elisa; Dubbioso, Raffaele; Madsen, Kristoffer Hougaard; Svolgaard, Olivia; Raffin, Estelle; Andersen, Kasper Winther; Karabanov, Anke Ninija; Siebner, Hartwig Roman (Frontiers in Neurology, 2020)
Objective: We employed dual-site TMS to test whether ipsilateral functional premotor-motor connectivity is altered in relapsing-remitting Multiple Sclerosis (RR-MS) and related to central fatigue. Methods: 12 patients with RR-MS and 12 healthy controls performed a visually cued Pinch-NoPinch task performed with their right hand. Single-site TMS to left primary motor cortex (M1) or dual-site TMS to ipsilateral dorsal premotor cortex (PMd) and M1 was given during the reaction time (RT) period of Pinch and No-Pinch trials. We traced context-dependent changes of corticospinal and premotor–motor connectivity, measuring the Motor-Evoked Potentials (MEPs) in the right first dorsal interosseus muscle. Central fatigue was evaluated with the Fatigue Scale for Motor and Cognitive Functions (FSMS). Results: In both groups, single-pulse TMS revealed a consistent increase in mean MEP amplitude during the RT period relative to a resting condition. Task-related corticospinal facilitation increased towards the end of the RT period in Pinch trials, while it decreased in No-Pinch trials. Again, this modulation of MEP facilitation by trial type was comparable in patients and controls. Dual-site TMS showed no significant effect of a conditioning PMd pulse on ipsilateral corticospinal excitability during the RT period in both groups. Patients showed a trend towards a relative attenuation in functional PMd-M1 connectivity at the end of RT period in No-Pinch trials which correlated positively with the severity of motor fatigue (r=0.69; p=0.007). Conclusions: Dynamic regulation of corticospinal and ipsilateral PMd-M1 excitability is preserved in patients with RR-MS. MS-related fatigue scales with an attenuation of premotor-to-motor functional connectivity during cued motor inhibition. Significance: The temporal context-dependent modulation of ipsilateral premotor-motor connectivity as revealed by dual-site TMS of ipsilateral PMd and M1 constitutes a promising neurophysiological marker of fatigue in MS.